Autonomy and Accountability of Public Enterprises in India: Examining the Autonomy-Accountability Relationship in Indian Public Enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The hidden suspicion in this paper is that autonomy and accountability are both principal essentials for the compelling working of state‐owned enterprises. The paper initially looks at the customary, dichotomous way to deal with the autonomy‐accountability problem. This approach sets the relationship as process arranged, inescapable, quantitative and in view of from the earlier controls. This thorough paper is an endeavor to give an outline of the plan, development and usage of and the instrument set up to guarantee the satisfaction of the goal set down in the plan of the concede of Autonomy versus the Status of Autonomy in India. This paper features exceptionally late activities relating to the concede of Autonomy versus the Status of Autonomy in India.